P657 Persistence in smoking cessation in inflammatory bowel disease (IBD). (21st January 2022) - González Muñoza, C; Gely, C; Teller, M; Mombiela, A; Roig, C; Lopez-Faba, A; Bertoletti, F; Gordillo, J; Garcia-Planella, E
Abstract: Background: Smoking Habit (SH) is a relevant epidemiological factor in IBD, so it is recommended to quit. We have no data on the persistence of its long-term abandonment. Methods: All patients of our hospital registred in the ENEIDA registry (spanish national IBD registry) with active SH at time of diagnosis were identified. Ex-smokers (> 6 months of abstinence) were invited to participate by telephone contact and epidemiological and SH data were recorded using medical records and telephone survey. The Fargeström Test for Nicotine Dependence (FTND) was used to grade the degree of addiction. Results: 122 ex-smokers [88 Crohn Disease (CD), 33 Ulcerative Colitis (UC)] were included, the mean age of SH abandonment (SHA) was 41 years (33–48), lower in CD (38 years) compared to UC (46) (p-value 0.002). The mean time from diagnosis to SHA was 72 months in CD and 98 in UC. Patients had a 2-point degree of FTND addiction, higher in CD (p-value 0.063), with 80% of them working. In CD, the main motivation was medical indication as a specific treatment (28%) and for general health advice (23%); in UC were general health advice (45%) followed by associated comorbidities (15%). 90% of the cohort managed to quit smoking on their own and only 11% needed pharmacological help. 60% explained a relapse, on average at 12 months (3–36), with a higher rate in CD (46%) compared with UC (24%) (p-value 0.029) despite a longer mean follow-up of patients with UC (114 VS 168, p-value 0.035). 39% of them referred to be living with a smoker at the time of relapse. The only factor of those assessed that directly impacted the risk of relapse was a higher score on the FTND (p-value 0.027). Conclusion: - The overall risk of relapse is 60%, half of which during the first year. Patients with CD have a higher risk, possibly due to a higher degree of addiction. - The only factor associated with relapse in (SH) was a higher FTND score. - SHA is delayed in relation to the diagnosis of IBD.